Social Media, Religion, and Student Mental Health: Associations with Anxiety and Burnout - Khotibul Umam, Aguswan; Irfan Achfandhy, Mochammad; Yuliasari, Alfiyana; Jamiah, Ririn (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
Religion can support mental well-being, yet social media exposes students to diverse religious messages whose psychological effects may differ by content type. Prior research often treats religion as a single construct and seldom examines how specific online religious content relates to anxiety and burnout. This study investigated associations between distinct categories of religious content on social media and levels of anxiety and burnout among students at Islamic Higher Education Institutions (PTKI) in Lampung, Indonesia. A quantitative survey of 1,098 PTKI students assessed exposure to five content types: compassion–tranquility, educational, inspirational–motivational, fear–punishment, and ritual–worship. Anxiety and burnout were measured using the Social Anxiety Scale for Adolescents (SAS-A; α=.91) and the Maslach Burnout Inventory–Student Survey (MBI-SS; α=.86). Hierarchical multiple regression tested linear, quadratic, and interaction effects, adjusting for age, institutional type, platform, frequency, and daily duration. For anxiety (final R²=.037), motivational content predicted lower anxiety, whereas fear–punishment—and to a lesser extent educational—content predicted higher anxiety. Compassion–tranquility and ritual–worship were non-significant. For burnout (final R²=.079), the control variables explained most of the variance. Daily social media duration was positively associated with burnout, and platform differences emerged (higher on Facebook, lower on YouTube compared with TikTok). Private PTKI students reported lower burnout than state PTKI students. Although no nonlinear or interaction effects were found for anxiety, burnout showed curvilinear patterns (Compassion²↑, Fear²↓) and buffering by motivational content. Overall, associations between religious content exposure and mental health were small yet consistent. Findings suggest value in promoting motivational, skills-oriented messages, limiting fear-based framing, tailoring content to platform dynamics, and encouraging balanced screen time. Future research should incorporate broader psychosocial factors and longitudinal designs to clarify causal mechanisms.